Answers

2014-07-23T23:58:59+08:00
Cot² Ф =    csc² Ф -1
           =      1/sin² - 1
                    [ 1/1 -cos² ] -1                ^  sin²Ф + cos²Ф = 1

sinФ(1 + cot²Ф) =  sinФ( 1 + cos²Ф/sin²Ф)
                               sinФ + cos²Ф/sinФ
                                ( sin²Ф + cos²)sinФ  =    1/sinФ
                                                                   = 1/(√1 - cos²Ф)
cscФsecФ - cotФ
1/sinФ1/cos -  cosФ/sinФ
 1/sinФcosФ - cosФ/sinФ
     1- cos²Ф/sinФ  =      sin²Ф/sinФ
                              =    sinФ  =     ( √1- cos² Ф)










                          
0